A comprehensive analysis on the relationship between BDE-209 exposure and erectile dysfunction. (December 2022) - Zhou, Xuan; Song, Lebin; Cong, Rong; Luan, Jiaochen; Zhou, Xiang; Wang, Yichun; Yao, Liangyu; Zhang, Xu; Ren, Xiaohan; Zhang, Tongtong; Yu, Mengchi; Song, Ninghong
Abstract: Decabromodiphenyl ether (mainly BDE-209) is a commonly used brominated flame retardant in various industrial products. Although its damage to the reproduction system has been established, its effect on erectile function remains unclear. The present study investigated whether BDE-209 induced erectile dysfunction in male SD rats and the underlying mechanisms. Pubertal male rats were exposed to BDE-209 orally (0, 5, 50, and 500 mg/kg/day) for 28 days and the ICP (intracavernous pressure) and MAP (mean arterial pressure) were measured. After the rats were euthanized, the fibrosis and apoptosis levels were evaluated. Additionally, the endothelial function of the rat vascular endothelium cells and the human umbilical vein endothelial cells were impaired after treatment with 50 μM and 100 μM BDE-209. Moreover, the bioinformatics based on CTD database and ChIP-X Enrichment Analysis, version 3 (ChEA3) and molecular docking analysis demonstrated that 5 transcription factors (NFKB1, NR3C1, E2F5, REL, IRF4) might regulate endothelial function by affecting the expression of interactive genes (BCL-2, CAP3, CAT, TNF, MAPK1, and MAPK3). In summary, the present study demonstrated that BDE-209 might affect downstream interactive genes by binding to transcription factors, leading to corpus cavernosum endothelial dysfunction, thus contributing to erectile dysfunction in rats. Graphical abstract: Image 1 Highlights: We used bioinformatics methods to predict and screen the genes responsible for BDE-209. We verified the effects of BDE-209 on erectile function. We validated the interactive genes using molecular docking and in vitro experiments. We estimated the function of the selected gene in cell lines.